Investigation of probing repeatability inside a micro-hole by changing probe approach direction for a local surface interaction force detection type microprobe - Aruga, Masakazu; Ito, So; Kato, Daichi; Matsumoto, Kimihisa; Kamiya, Kazuhide (Frontiers in Manufacturing Technology, 2023)
The inner diameter measurement of the micro-hole was performed by a tactile microprobing system using a method of the local surface interaction force detection. The inner diameter of the micro-hole was calculated by the least square method based on the probing coordinates obtained by a custom-made micro-coordinate measuring machine. The dispersion of the probing coordinates was investigated by changing the probe approaching direction with respect to the normal direction of the inner side of the micro-hole. During the probing inside the micro-hole, it was confirmed that the dispersion of the probing coordinates increased when the disagreement between the probe approaching direction and the normal direction of the micro-hole at the measured point became large. The influence of the dispersion of the probing coordinates was evaluated through the uncertainty analysis of the inner diameter measurement. It was revealed that the uncertainty of the inner diameter measurement could be improved when limiting the disagreement between the probe approaching direction and the normal direction of the micro-hole to within ±pi/4 rad.